Plasma Levels of α-Synuclein, Aβ-40 and T-tau as Biomarkers to Predict Cognitive Impairment in Parkinson’s Disease - Chen, Nai-Ching; Chen, Hsiu-Ling; Li, Shau-Hsuan; Chang, Yen-Hsiang; Chen, Meng-Hsiang; Tsai, Nai-Wen; Yu, Chiun-Chieh; Yang, Shieh-Yueh; Lu, Cheng-Hsien; Lin, Wei-Che (Frontiers in Aging Neuroscience, 2020)
Objective In this study, we assessed plasma biomarkers to identify cognitive impairment in Parkinson’s disease (PD) patients by applying ultra-sensitive immunomagnetic reduction-based immunoassay (IMR). Methods The study enrolled 60 PD patients and 28 age- and sex-matched normal controls. Complete cognitive function assessments were performed on participants using the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating. PD patients with an MMSE score of ≦26 were defined as having cognitive impairment. Meanwhile, a 99mTc-TRODAT-1 scan was performed and plasma levels of Aβ-40, Aβ-42, T-tau, and α-synuclein were evaluated using IMR, subsequent correlation analyses were then performed. Results Compared with normal adults, PD patients have higher plasma levels of α-synuclein and T-tau, and a lower level of Aβ-40 (p < 0.05). Plasma levels of α-synuclein (r = −0.323, p = 0.002), Aβ-40 (r = 0.276, p = 0.01), and T-tau (r = −0.322, p = 0.002) are significantly correlated with MMSE scores. The TRODAT scan results, including visual inspection and quantification, revealed significant correlations between Aβ-40 and PD. Multiple regression analysis showed that the plasma levels of Aβ-40 (OR = 0.921, 95% CI = 0.879–0.962), α-synuclein (OR = 3.016, 95% CI = 1.703–5.339), and T-tau (OR = 1.069, 95% CI = 1.026–1.115) were independently associated with PD patients with cognitive impairment. The cutoff values for predicting cognitive deficits in PD patients were 45.101 pg/ml of Aβ-40, (Area under curve (AUC) = 0.791), 0.389 pg/ml of α-synuclein, (AUC = 0.790), and 30.555 pg/ml of T-tau (AUC = 0.726). Conclusion Plasma levels of α-synuclein, Aβ-40, and T-tau are potential biomarkers to detect cognitive impairment in PD patients.